2010
DOI: 10.1186/1476-8518-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of high affinity human monoclonal antibodies that neutralize staphylococcal enterotoxin B

Abstract: BackgroundStaphylococcal enterotoxins are considered potential biowarfare agents that can be spread through ingestion or inhalation. Staphylococcal enterotoxin B (SEB) is a widely studied superantigen that can directly stimulate T-cells to release a massive amount of proinflammatory cytokines by bridging the MHC II molecules on an antigen presenting cell (APC) and the Vβ chains of the T-cell receptor (TCR). This potentially can lead to toxic, debilitating and lethal effects. Currently, there are no preventativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 30 publications
0
31
1
Order By: Relevance
“…They exhibited similar affinity constants for AT, thus precluding a similar comparison between affinity and potency. One example where affinity correlated with antitoxin potency was reported for MAbs against staphylococcal enterotoxin B (SEB); however, the potencies of the different MAbs were not examined in vivo (12). The number of MAbs compared in our study and the Drozdowski study (12) is small, yet the results provide support for the hypothesis that in some instances an increase in affinity will result in increased potency.…”
Section: Discussioncontrasting
confidence: 29%
“…They exhibited similar affinity constants for AT, thus precluding a similar comparison between affinity and potency. One example where affinity correlated with antitoxin potency was reported for MAbs against staphylococcal enterotoxin B (SEB); however, the potencies of the different MAbs were not examined in vivo (12). The number of MAbs compared in our study and the Drozdowski study (12) is small, yet the results provide support for the hypothesis that in some instances an increase in affinity will result in increased potency.…”
Section: Discussioncontrasting
confidence: 29%
“…In some cases, a combination of mAbs was required to achieve optimal protection (8 -13). However, the administration of potent neutraliz-ing SEB-specific mAbs, either individually or as cocktails (14,15), constitutes a challenge, because the onset of life-threatening symptoms after aerosol exposure occurs within 24 h (16). Given the short window for therapeutic intervention after exposure, lead clinical mAb candidates need to be optimized for postexposure treatment against SEB intoxication.…”
Section: Staphylococcal Enterotoxin B (Seb)mentioning
confidence: 99%
“…Previous studies using human anti-SEB antibodies reported by other investigators showed partial protection even when used in a prophylactic setting (33). In another report by Drozdowski et al (34), a human anti-SEB antibody protected 90% of mice when administered at the time of challenge with SEB, whereas the protection dropped to 50 or 10% when antibody was administered 30 min or 1 hour postexposure, respectively. In contrast, three of the lead human anti-SEB antibodies reported here showed complete protection over a wide range of challenge doses when administered 1 h postchallenge.…”
Section: Discussionmentioning
confidence: 85%